Anode materials for potassium‐ion batteries: Current status and prospects. Issue 3 (11th June 2020) - Sha, Mo; Liu, Long; Zhao, Huaping; Lei, Yong
Abstract: Potassium‐ion batteries (KIBs) as one of the most promising alternatives to lithium‐ion batteries have been highly valued in recent years. However, progress in KIBs is largely restricted by the sluggish development in anode materials. Therefore, it is imperative to systematically outline and evaluate the recent research advances in the field of anode materials for KIBs toward promoting the development of high‐performance anode materials for KIBs. In this review, the recent achievements in anode materials for KIBs are summarized. The electrochemical properties (ie. charge storage mechanism, capacity, rate performance, and cycling stability) of these reported anode materials, as well as their advantages/disadvantages, are discerned and analyzed, enabling high‐performance KIBs to meet the requirements for practical applications. Finally, technological developments, scientific challenges, and future research opportunities of anode materials for KIBs are briefly reviewed. Abstract : Recently, potassium‐ion batteries (KIBs) have attracted considerable attention due to their low‐cost, fast ion conductivity in electrolyte and high operating voltage. Anode materials play a significant role in determining the overall electrochemical property of KIBs. This review provides the recent advancements of anode materials for KIBs. Furthermore, the challenges and prospects of these anode materials are also discussed.